THE EFFECT OF YOUTUBE EDUCATIONAL CHANNEL ON STUDENTS’ LISTENING COMPREHENSION AT SMAN 8 LUWU TIMUR - Astuty, Ratri Septi; Muliati, Andi; Muhayyang, Maemuna (State University of Makassar, 2022)
The objective of this study was to determine the effect of YouTube educational channel on students’ listening comprehension. This research method was Pre- experimental design. The population of this research was the eleventh grade students of SMAN 8 Luwu Timur in the academic year 2022/2023 through a random sampling technique. The sample of this research is 30 students from XI MIPA 1. The instrument of this research was listening test, which delivered as the pretest and the post-test. The research findings showed that using YouTube educational channel in learning listening was significant to improve students’ listening comprehension. It was proved that the mean score of students’ pretest was 64.17 and the mean score of students’ posttest was 85.17. From that data, it could be concluded that the use of YouTube educational channel could improve students’ listening comprehension. Keywords— YouTube Educational Channel, Listening Comprehension